Enhancing organizational efficiency and quality control through the implementation of total quality management: A strategic approach to sustainable improvement - Waheed, Muhammad; Abbas, Mutahir (YAYASAN MITRA PERSADA NUSANTARA, 2024)
This study explores the strategic implementation of Total Quality Management (TQM) as a means to enhance organizational efficiency and strengthen quality control mechanisms. In an increasingly competitive business environment, organizations must adapt to quality-centric frameworks that not only improve operational performance but also ensure long-term customer satisfaction and sustainability. The primary aim of this research is to assess how the principles and practices of TQM contribute to increased efficiency, process optimization, and quality assurance across various organizational levels. A qualitative-descriptive method was employed, involving a combination of case study analysis and semi-structured interviews with quality managers from three manufacturing firms actively implementing TQM practices. Key components analysed include continuous improvement (Kaizen), customer focus, employee involvement, process standardization, and top management commitment. Data were coded and thematically analysed to identify recurring patterns and strategic outcomes of TQM application. The findings reveal that the successful implementation of TQM results in measurable improvements in productivity, defect reduction, cost efficiency, and employee morale. Firms that consistently applied quality control tools such as Six Sigma, PDCA cycles, and root cause analysis reported enhanced decision-making and better responsiveness to customer demands. The role of leadership and internal communication was also identified as a critical success factor in embedding quality culture. In conclusion, this study affirms that TQM is not merely a set of tools but a holistic organizational philosophy that, when implemented effectively, leads to sustainable competitive advantage. The research recommends continuous training, inclusive leadership, and clear performance metrics as key enablers for optimizing TQM outcomes.